Advocacy for Smoke-Free Areas by the Indonesia Tobacco Control Research Network (ITCRN) in Situbondo Regency: Challenges and Commitments of Stakeholders [Accepted] - Eni - Purwaningsih; Azizatul - Hamidiyah; Rohmetal - Wahyudi; Abdillah - Hasan (Health Dynamics, 2026)
Background: Smoking is a major risk factor for non-communicable diseases (NCDs) in Indonesia, with a high prevalence of smoking, including in Situbondo Regency. The increase in cases of pneumonia due to exposure to cigarette smoke exacerbates health problems in this area. The Smoke-Free Area (KTR) policy aims to create a smoke-free environment to protect the community, especially children and vulnerable groups. This study aims to analyse the advocacy process in the ratification of the KTR Regional Regulation (Perda) in Situbondo Regency, as well as the challenges and commitments faced by stakeholders.  Methods: A qualitative approach with a case study design was used. Data collection was conducted through unstructured interviews, participatory observation, and analysis of documents related to KTR policy. Participants consisted of stakeholders such as government officials, members of the Regional People's Representative Council (DPRD), and civil society organisations. Results: This study found that despite strong commitment from local government and the community, the main challenges were public misunderstanding of the scope of the KTR policy and its economic impact on tobacco farmers. In addition, active community participation, particularly by the Children's Forum, played an important role in supporting advocacy for this policy. Conclusions: The successful enactment and implementation of the KTR Regional Regulation in Situbondo Regency requires strong cross-sectoral collaboration and effective education strategies to increase public understanding and support for more inclusive tobacco control policies.